Islamic Boarding School-Based Madrasah: Policy Efforts to Reform the Superior Education Model - M. Yunus Abu Bakar; Yeyen Afista (Al-Hayat: Journal of Islamic Education, 2020)
Madrasah is an alternative educational institution and has the same opportunity to become an educational institution taken into account in social change dynamics. However, as a logical consequence, madrasas must develop each sector to achieve its organizational goals. This study examines the opportunities and challenges of developing madrasas, particularly those based on an Islamic boarding school. This study is a literature study, so that the method of analyzing data is by reviewing and collecting information from various references, both books and scientific articles, which are used as a material in studying and adding conceptual insights related to the opportunities and challenges of developing Islamic boarding school-based madrasas in the modern era. The literature review results show that in developing the education system into a preeminent institution and maintaining its existence, madrasas in Islamic boarding school are required to be open and accommodate the community's aspirations and demands. Madrasah needs to develop themselves to become high quality and superior madrasas and a bridge that connects with the national education system, especially those related to students' moral and personality development. This is understandable because the community hopes that educational institutions in Islamic boarding school are religious experts, have morals, and have future skills.